A Smile Analysis in Completely Edentulous Patients Treated by Graduate Students - Ditty J Mary1 , Suresh Venugopalan2 , Nashra Kareem3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
To evaluate smile analysis in completely edentulous patients. Smile is a main component in presentations ofa human being favoring social acceptance. A non harmonic smile decreases the beauty of the face causingdiscomfort in the social activity Edentulous in a condition of being toothless. Details were collected frompatients visiting dental college and reviewed patient records who underwent denture treatment betweenjune 2019 and march 2020. In the present study we analyzed visibility, fullness, teeth size, buccal corridorspace and smile line.. The study reviewed the patients who had undergone treatment between June 2019– April 2020.Data was entered in a methodological manner and was verified manually. The available datawas subjected to statistical tests using - Chi square test statistical software- SPSS software by IBM.Thepresent study indicates the dentures constructed by training students are good at fullness, visibility and teethselection criteria but there is lack of adequate buccal corridor space and smile curves being incorporatedinto dentures.